(untitled) (LEARNing Landscapes, 2019)
Acting reflexively implies a “self-critical and self-conscious stance” (Glass, 2015, p. 555) of recognizing myself within a research process as an intentional participant-practitioner of generating knowledge. This article attempts to reveal visual evidence across a landscape of textual references and material implementations as a process of the what and how of knowing. My aim is to affirm the intentionality of my reflexive praxis as a way of knowing and becoming through committed intertextual inquiry and discovery.